Polymer film for azeotropic mixture and preparation method thereof

By copolymerizing polyimide with sodium bicarbonate and covering porous nanosilicon sol, the problem of high energy consumption and high cost of removing excess methanol in the reaction between methanol and isobutene in the prior art is solved, and efficient separation of azeotropic mixture is achieved, reducing energy consumption and cost, and extending the service life of the film.

CN119656880APending Publication Date: 2025-03-21中科瀚喆(常州)净化技术有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979196.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art When removing excess methanol in the reaction of methanol with isobutene, it has high energy consumption and high cost, and it is difficult to efficiently separate the azeotropic mixture.

Method used

Polyimide and sodium bicarbonate are used to form a separation layer, and the porous nanosilicon sol is covered with the separation layer. Through the interaction of sodium ions and nanosilicon dioxide, the permeability and separation efficiency of the separation layer are improved.

Benefits of technology

It improves the separation efficiency of azeotropic mixture, reduces energy consumption and cost, and extends the service life of the polymer film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656880A_ABST
    Figure CN119656880A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of membrane separation, and particularly relates to a polymer membrane for an azeotropic mixture and a preparation method of the polymer membrane. Preparing porous nano silica sol; fully infiltrating the porous nano-silica sol and a cross-linking agent into the separation layer, and cross-linking to obtain the porous nano-silica gel. The method can be used for separating the azeotropic mixture of the methanol and the hydrophobic organic matter with the kinetic diameter larger than that of the methanol, and has a specific adsorption tendency to formaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of membrane separation, and in particular relates to a polymer membrane for azeotropic mixture and a preparation method thereof. Background Art

[0002] Methyl tert-butyl ether (MTBE) plays a key role as an octane enhancer in the production of unleaded gasoline, which can effectively reduce air pollution and optimize fuel combustion. Typically, the synthesis of MTBE involves the reaction between methanol (MeOH) and isobutylene. In order to ensure efficient conversion, >20% methanol is usually used to make methanol excessive in the system, which leads to the formation of an azeotrope containing 14.3wt% methanol. In order to remove excess methanol, traditional methods such as azeotropic distillation, reactive distillation and water washing are adopted, but these methods have the problems of high energy consumption and extremely high cost. On this basis, pervaporation separation membranes are a promising technology for separating such azeotropes. For decades, people have been committed to combining fillers with excellent specific separation capabilities with polymers with simple preparation processes to prepare membrane materials with high separation efficiency. Summary of the invention

[0003] The present invention mainly provides a polymer membrane for separating an azeotropic mixture of methanol and a hydrophobic organic compound having a kinetic diameter greater than that of methanol and a preparation method thereof. The technical scheme is as follows:

[0004] A method for preparing a polymer membrane for an azeotropic mixture comprises the following steps: copolymerizing a polyimide monomer with sodium bicarbonate and obtaining a separation layer after heat treatment; preparing a porous nano-silica sol; and fully infiltrating the porous nano-silica sol and a cross-linking agent into the separation layer and cross-linking the separation layer to obtain the membrane.

[0005] Furthermore, the support body includes one of polyethersulfone, polysulfone, polyvinylidene fluoride or polyacrylonitrile.

[0006] Further, the following steps are included:

[0007] a. Grind 2,4,6-triaminopyrimidine and sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve pyromellitic anhydride in low-temperature N,N-dimethylacetamide to obtain a pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, apply it to a support, evaporate the solvent on the coating layer, and heat treat it to obtain a support containing a separation layer;

[0008] b. Mix the porous nano-silica sol with glutaraldehyde, add hydrochloric acid to adjust the pH to 3 to 5, and then apply it to the separation layer on the surface of the support, and let it stand at 2 to 10°C for 2 to 4 hours to fully wet the separation layer;

[0009] c. Dry the support after fully infiltrating the separation layer at 25-35°C until the volume no longer decreases, then raise the temperature to 50-80°C and continue drying for 1-3 hours.

[0010] Furthermore, the low temperature in step a is 0-8°C; the evaporation of the solvent in step a is performed by fully drying at 160-180°C; and the heat treatment in step a is performed by heating the mixture to 300-350°C at a rate of 10-20°C / min and treating the mixture for 2-4h.

[0011] Furthermore, the concentration of the pyromellitic anhydride solution is 10-20 g / mL; the mass ratio of the sodium bicarbonate to the 2,4,6-triaminopyrimidine is 1:2-5; and the molar ratio of the 2,4,6-triaminopyrimidine to the pyromellitic anhydride is 1:1.2-1.8.

[0012] Furthermore, the concentration of porous nano-silica in the porous nano-silica sol in step b is 20-50wt%; the mass ratio of porous nano-silica to glutaraldehyde in the porous nano-silica sol is 10-30:1.

[0013] Furthermore, the preparation of the porous nano-silica sol comprises the following steps:

[0014] Hexadecyltrimethylammonium bromide and triethanolamine are added to water, and then n-pentanol is added thereto, and the mixture is fully mixed and dissolved, and then ethyl orthosilicate is added dropwise to the system, and the mixture is reacted at room temperature for 4 to 8 hours; the reaction product is separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica is placed in water, and ultrasonically dispersed to obtain a porous nano-silica sol.

[0015] Furthermore, the mass ratio of hexadecyltrimethylammonium bromide to triethanolamine is 1:0.1-0.8; the mass ratio of n-pentanol to triethanolamine is 1:0.1-0.5; and the mass ratio of hexadecyltrimethylammonium bromide to tetraethyl orthosilicate is 1:8-12.

[0016] A polymer membrane for azeotropic mixture prepared by the above method comprises a sodium-containing polyimide separation layer and porous nano-silicon covering the separation layer; the separation layer covers a porous support body; and the average pore size of the separation layer is 0.5-0.6nm.

[0017] An application of the above polymer membrane for azeotropic mixture in separating azeotropic mixture containing methanol, for separating azeotropic mixture of methanol and hydrophobic organic matter with a kinetic diameter larger than that of methanol.

[0018] By adopting the above scheme, the method of the present invention has the following advantages:

[0019] 1. The present invention copolymerizes sodium bicarbonate and polyimide, and generates holes on the film formed after polymerization due to the volatilization of water molecules, thereby improving the permeability of the polyimide film and improving the separation efficiency of the azeotropic mixture.

[0020] 2. The polyimide of the present invention can be complexed with sodium ions. Before polymerization, the sodium ions can be evenly dispersed with the polymerization precursor, which promotes the uniform dispersion of the residual sodium in the separation layer. Thus, the dispersion of silicon dioxide on the separation layer is improved by the interaction between sodium ions and nano-silicon dioxide, thereby preventing the aggregation of silicon dioxide.

[0021] 3. The polyimide of the present invention is complexed with sodium ions to improve the interfacial adhesion between the sodium compound and the polyimide. Under the action of sodium ions and silicon dioxide, the binding force between silicon dioxide and the separation layer is enhanced, the desorption of the sodium compound and silicon dioxide is reduced, and the service life of the polymer membrane is increased.

[0022] 4. When the sodium ions migrate to the surface of the nano-silica particles When the nano-silica particles and the sodium ions form an exchange of positive and negative charges, under the influence of electrostatic force, van der Waals force, hydrogen bond and other forces, the nano-silica particles of the present invention interact with the sodium ions. Under the premise that the sodium ions are fully dispersed, the silica also tends to disperse, which helps to evenly distribute the silica on the separation layer.

[0023] 5. The silicon dioxide of the present invention is a Lewis acid, has similar properties to Lewis acid, has excellent affinity with methanol, and can produce a unique attraction to methanol when separating an azeotropic mixture containing methanol, has high separation efficiency, and has a strong specific adsorption capacity for methanol.

[0024] 6. The separation layer and the fillers on the membrane of the present invention are both hydrophilic, and methanol has similar properties to water. The permeation rate of methanol on the polymer membrane of the present invention is faster and the selectivity is higher.

[0025] 7. The preparation method of the polymer film of the present invention is simple, the cost of raw materials and equipment is low, and the polymerization of polyimide and the decomposition of sodium bicarbonate are carried out in the same scene. The node of complete decomposition of sodium bicarbonate is controlled by rapid temperature increase to achieve full utilization of energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope photograph of Example 1 of the present invention;

[0027] Figure 2 This is a scanning electron microscope photograph of Example 2 of the present invention;

[0028] Figure 3 This is a scanning electron microscope photograph of Example 3 of the present invention. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1: (1) Preparation of polyacrylonitrile nanoporous support;

[0031] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0032] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0033] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0034] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0035] Example 2: (1) Preparation of polyacrylonitrile nanoporous support;

[0036] (2) Grind 5 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 7 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0037] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0038] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0039] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0040] Example 3: Preparation of polyacrylonitrile nanoporous support;

[0041] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, apply it to a support, dry it at 170° C. to evaporate the solvent on the coating layer, heat it to 350° C. at a rate of 15° C. / min, and heat treat it for 2 h to obtain a support containing a separation layer;

[0042] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0043] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0044] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0045] Example 4: (1) Preparation of polyacrylonitrile nanoporous support;

[0046] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, apply it to a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 4 hours to obtain a support containing a separation layer;

[0047] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0048] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0049] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0050] Example 5: (1) Preparation of polyacrylonitrile nanoporous support;

[0051] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0052] (3) 1 g of hexadecyltrimethylammonium bromide and 0.7 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of ethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0053] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0054] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0055] Example 6: (1) Preparation of polyacrylonitrile nanoporous support;

[0056] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0057] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was thoroughly mixed and dissolved, and then 8 g of ethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 50 wt% porous nano-silica sol;

[0058] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0059] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0060] Example 7: (1) Preparation of polyacrylonitrile nanoporous support;

[0061] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0062] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 4 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0063] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0064] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0065] Example 8: (1) Preparation of polyacrylonitrile nanoporous support;

[0066] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0067] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0068] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 10° C. for 2 h to fully infiltrate the separation layer;

[0069] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0070] Example 9: (1) Preparation of polyacrylonitrile nanoporous support;

[0071] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0072] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0073] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 4 h to fully infiltrate the separation layer;

[0074] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 1 hour.

[0075] Example 10: (1) Preparation of polyacrylonitrile nanoporous support;

[0076] (2) Grind 3 g of 2,4,6-triaminopyrimidine and 1 g of sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve 4 g of pyromellitic anhydride in N,N-dimethylacetamide at 3-5° C. to obtain a 15 g / mL pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, and then coat it on a support, fully dry it at 170° C. to evaporate the solvent on the coating layer, and then heat it to 300° C. at a rate of 15° C. / min, and heat treat it for 2 hours to obtain a support containing a separation layer;

[0077] (3) 1 g of hexadecyltrimethylammonium bromide and 0.2 g of triethanolamine were added to 50 mL of water, and then 2 g of n-pentanol was added thereto, and the mixture was fully mixed and dissolved, and then 8 g of tetraethyl orthosilicate was added dropwise to the system, and the mixture was reacted at room temperature for 8 h; the reaction product was separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica was placed in water, and ultrasonically dispersed to obtain a 30 wt% porous nano-silica sol;

[0078] (4) 100 g of porous nano-silica sol was mixed with 0.5 g of glutaraldehyde, and hydrochloric acid was added to adjust the pH to 4, and then coated on the separation layer on the surface of the support, and allowed to stand at 2° C. for 2 h to fully infiltrate the separation layer;

[0079] (5) Dry the support after fully infiltrating the separation layer at 30° C. until the volume no longer decreases, then heat it to 60° C. and continue drying for 3 h.

[0080] Example of support preparation: 5 g of 50 kDa polyacrylonitrile powder and 1.67 g of polyethylene glycol 600 are completely dissolved in 26.66 mL of N,N-dimethylformamide to generate a polymer casting solution; the polymer casting solution is stirred at 60°C for 12 hours, and then degassed at room temperature for 24 hours to form a uniform casting solution; then, the uniform casting solution is cast onto a non-woven fabric and diffused into deionized water to induce phase inversion. After completion, it is at least rinsed with water to obtain a polyacrylonitrile nanoporous support.

[0081] Example sample test:

[0082] Example <![CDATA[Total flux (g / m 2 ·h)]]> Separation factor 1 86.4 234 2 65.8 251 3 75.3 192 4 91.4 221 5 82.6 264 6 64.7 375 7 88.5 220 8 97.1 183 9 71.9 328 10 93.6 289

[0083] As can be seen from the above table, compared with Example 1, the total flux of Example 1 with more sodium bicarbonate content is higher than that of Example 2, indicating that the copolymerization and heat treatment of sodium bicarbonate can increase the flux of the polymer membrane. The total flux of Example 3 with a higher heat treatment temperature decreased, indicating that the higher temperature makes the airway formed by the decomposition of sodium bicarbonate less timely than that of Example 1, and the separation factor of Example 3 also decreases, which may be because the airway is closed earlier and there are fewer sodium ions exposed to contact with silica. The total flux of Example 4 with a longer time increased slightly, but the increase was not obvious.

[0084] In Example 6, the silicon content in the silica sol coated on the surface of the separation layer is higher than that in Example 1, and its total flux decreases, but its separation factor increases significantly, indicating that the silica introduced by the present invention has a significant specific adsorption tendency for methanol. In Example 8, the ambient temperature during static infiltration is higher, and the hydrochloric acid and the sodium carbonate remaining in the separation layer react faster, the flux increases, but the separation factor decreases significantly. The faster reaction rate may make the pore size distribution of the pores generated on the surface more uneven, and the speed needs to be controlled to ensure the separation efficiency. In Example 9, more time was spent on static infiltration, and its separation factor also increased significantly, indicating that the static infiltration step is conducive to improving the separation efficiency of the polymer membrane for methanol. In Example 10, the time for continuing heat treatment after silica sol treatment is longer than that of Example 1, and its total flux and separation factor both increase, indicating that the heat treatment at this time is conducive to the escape of carbon dioxide gas produced by sodium carbonate, increases membrane flux, and helps to expose silica, forming an interaction with methanol.

[0085] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a polymer film for an azeotropic mixture, characterized in that: The method comprises the following steps: copolymerizing a polyimide monomer with sodium bicarbonate on a support, and obtaining a separation layer after heat treatment; Prepare porous nano-silica sol; fully infiltrate the porous nano-silica sol and the cross-linking agent into the separation layer, and cross-link to obtain the result.

2. The method for preparing a polymer film for an azeotropic mixture according to claim 1, characterized in that: The support body includes one of polyethersulfone, polysulfone, polyvinylidene fluoride or polyacrylonitrile.

3. The method for preparing a polymer film for an azeotropic mixture according to claim 1, characterized in that: The following steps are involved: a. Grind 2,4,6-triaminopyrimidine and sodium bicarbonate until they are uniformly mixed to obtain a mixed powder; dissolve pyromellitic anhydride in low-temperature N,N-dimethylacetamide to obtain a pyromellitic anhydride solution; maintain low temperature, add the mixed powder to the pyromellitic anhydride solution, disperse it uniformly, apply it to a support, evaporate the solvent on the coating layer, and heat treat it to obtain a support containing a separation layer; b. Mix the porous nano-silica sol with glutaraldehyde, add hydrochloric acid to adjust the pH to 3 to 5, and then apply it to the separation layer on the surface of the support, and let it stand at 2 to 10°C for 2 to 4 hours to fully wet the separation layer; c. Dry the support after fully infiltrating the separation layer at 25-35°C until the volume no longer decreases, then raise the temperature to 50-80°C and continue drying for 1-3 hours.

4. The method for preparing a polymer film for an azeotropic mixture according to claim 3, characterized in that: The low temperature in step a is 0-8°C; the solvent removal in step a is fully dried at 160-180°C; the heat treatment in step a is heated to 300-350°C at a rate of 10-20°C / min and treated for 2-4h.

5. The method for preparing a polymer film for an azeotropic mixture according to claim 3, characterized in that: The concentration of the pyromellitic anhydride solution is 10-20 g / mL; the mass ratio of the sodium bicarbonate to the 2,4,6-triaminopyrimidine is 1:2-5; the molar ratio of the 2,4,6-triaminopyrimidine to the pyromellitic anhydride is 1:1.2-1.

8.

6. The method for preparing a polymer film for an azeotropic mixture according to claim 3, characterized in that: In step b, the concentration of porous nano-silica in the porous nano-silica sol is 20-50wt%; the mass ratio of porous nano-silica to glutaraldehyde in the porous nano-silica sol is 10-30:

1.

7. The method for preparing a polymer film for an azeotropic mixture according to claim 1, characterized in that: The preparation of the porous nano-silica sol comprises the following steps: Hexadecyltrimethylammonium bromide and triethanolamine are added to water, and then n-pentanol is added thereto, and the mixture is fully mixed and dissolved, and then ethyl orthosilicate is added dropwise to the system, and the mixture is reacted at room temperature for 4 to 8 hours; the reaction product is separated and collected, and then fully washed with an ethanol aqueous solution, and dried to obtain porous nano-silica; the porous nano-silica is placed in water, and ultrasonically dispersed to obtain a porous nano-silica sol.

8. The method for preparing a polymer film for an azeotropic mixture according to claim 7, characterized in that: The mass ratio of hexadecyltrimethylammonium bromide to triethanolamine is 1:0.1-0.8; the mass ratio of n-pentanol to triethanolamine is 1:0.1-0.5; the mass ratio of hexadecyltrimethylammonium bromide to ethyl orthosilicate is 1:8-12.

9. A polymer film for an azeotropic mixture prepared by the method according to any one of claims 1 to 8, characterized in that: The invention comprises a sodium-containing polyimide separation layer and porous nano-silicon covered on the separation layer; the separation layer is covered on a porous support body; and the average pore size of the separation layer is 0.45-0.6nm.

10. Use of the polymer membrane for azeotropic mixture according to claim 9 in separating azeotropic mixture containing methanol, characterized in that: Separation of azeotropic mixtures of methanol and hydrophobic organic compounds with a kinetic diameter greater than methanol.